If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(b + -9) + 2 = 3 Reorder the terms: -1(-9 + b) + 2 = 3 (-9 * -1 + b * -1) + 2 = 3 (9 + -1b) + 2 = 3 Reorder the terms: 9 + 2 + -1b = 3 Combine like terms: 9 + 2 = 11 11 + -1b = 3 Solving 11 + -1b = 3 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1b = 3 + -11 Combine like terms: 11 + -11 = 0 0 + -1b = 3 + -11 -1b = 3 + -11 Combine like terms: 3 + -11 = -8 -1b = -8 Divide each side by '-1'. b = 8 Simplifying b = 8
| 3u+4=2u-9 | | 20x+15=30x+10 | | 4(d+3)+2=10 | | 3(d-12)=d+24 | | 9b+10=1 | | 2p+8=6 | | 3x+26=x+4 | | 20+8=6 | | 2x-4x^2= | | 16-3t=-7t | | 18-5(x+1)=3(x-1) | | 10g-47-4g=16+3g | | 8x^3-6x+1=0 | | 22-4x=2x-4 | | w-5+3w=6w-1 | | 10c+5=4c-1 | | 3x+3=4x-6 | | 7(x-10)=21 | | 14*(2x+2)=1716+6*(x+2) | | x^2+6x+8=e^2 | | z^2+iz=0 | | 3.3x=6.5(10x+4) | | ln(2x^2+7x-4)=2+ln(x^2+x-12) | | -1+(2t+3)+2(t-3)= | | 7x+5=45+3x | | ln(x)+ln(x-3)=ln(40) | | 6(p-5)-(4p+9)=25 | | 11a+18b+6C+4C-4B-2A= | | 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= | | -3(x-5)+2(4x-8)=12 |